ANALISIS PENGARUH INFLASI, PDB, DAN NILAI TUKAR TERHADAP VOLUME EKSPOR KOPI DI INDONESIA - Zalfa Hasna Safitri Berutu (2023)
Exports have an important role in a country's economy, which is able to generate foreign exchange for Indonesia and can increase a country's economic income. Indonesia is also known as a country that has a wealth of natural resources. One of the leading natural resources that contributes greatly to export activities in Indonesia is coffee. The purpose of this research is to determine the effect of inflation, GDP, and the exchange rate on the volume of coffee exports in Indonesia. The object used is a sample data on the annual volume of coffee exports in Indonesia for the 1990-2021 period. This study uses datatime series with data analysis techniques in researchError Correction Model (ECM) with the help of toolsEviews 12 and Microsoft Excel. The results showed that (1) Inflation has a significant positive effect in the long term and short term on the volume of coffee exports in Indonesia. (2) Gross Domestic Product has a positive and significant effect in the long term and short term on the Export Volume of Coffee in Indonesia. (3) The Exchange Rate has no significant effect both in the long term and in the short term on the Export Volume of Coffee in Indonesia.